ANALISIS PERENCANAAN DANA ALOKASI UMUM TAMBAHAN DALAM PELAKSANAAN PEMBANGUNAN DI DESA KALICACING, KECAMATAN SIDOMUKTI, SALATIGA - DEWI SEPTININGSIH; DWI APRILLIA NINGRUM; KARIMATUS SA'DIYAH; FITRIYATUL KHASANAH; NUR KABIB (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
This study aims to analyze the planning of a general allocation additional fund in order of development at the civil office of Kalicacing, Salatiga. To analyze a compatibility of general additional allocation fund at the Kalicacing Civil Office, Sidomukti, Salatiga. Tthe method of a research is description qualitative method. The collection method with observation, interview and documentation. The chief of the village is an informant. The result of the research shows that the planning of general additional allocation fund in order to develop the village it has been made base on Musrenbang (a conference plan of development) so that it will appear a calculation budget plan to be realized. A planning of General Addiotional Allocation Fund at the civil office of Kalicacing, Sidomukti, Salatiga City is not appropriate base on the number 187/PMK.07/2018 of finance minister regulation. A General Additional Allocation Fund must be similar with a village fund because it has a similar meaning to give a prosperity to the people.